Last encounter and other stories - "Chowdhary, D.S." (Jalandhar, 1987)
The Last Encounter" is a work of fiction. The story is about a burglar, who planned a furtive operation to rob an empty house. As he broke into the house, he was taken aback to find that the family left for vacation leaving a lady.
Keywords: Short stories